2019
DOI: 10.1038/s41598-019-47481-1
|View full text |Cite
|
Sign up to set email alerts
|

Catalytically Competent Non-transforming H-RASG12P Mutant Provides Insight into Molecular Switch Function and GAP-independent GTPase Activity of RAS

Abstract: RAS mutants have been extensively studied as they are associated with development of cancer; however, H-RAS G12P mutant has remained untouched since it does not lead to transformation in the cell. To the best of our knowledge, this is the first study where structural/dynamical properties of H-RAS G12P have been investigated -in comparison to H-RAS WT , H-RAS G12D , RAF-RBD-bound and GAP-bound H-RAS WT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Herein, it is important to mention that exposed conformation of Y32 was not observed in the trajectories pertaining to RAF-RBD-bound HRAS WT as shown in our earlier study ( Ilter and Sensoy, 2019 ). Therefore, this finding suggests that exposure of Y32 might occlude the interaction interface formed between RAS and RAF-RBD.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Herein, it is important to mention that exposed conformation of Y32 was not observed in the trajectories pertaining to RAF-RBD-bound HRAS WT as shown in our earlier study ( Ilter and Sensoy, 2019 ). Therefore, this finding suggests that exposure of Y32 might occlude the interaction interface formed between RAS and RAF-RBD.…”
Section: Resultsmentioning
confidence: 63%
“…The most probable conformational state of the binding pocket pertaining to HRAS G12D was determined by using following reaction coordinates: distance measured between (i) side-chain oxygen of residue T35 and Pγ atom of GTP, (ii) backbone amide of the residue G60 and Pγ atom of GTP, which were used to point out different conformational states of the nucleotide-bindng pocket in our previous study ( Ilter and Sensoy, 2019 ). The frames, which represent different conformational states of the nucleotide-binding pocket with respect to the above-mentioned coordinates, were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Herein, it is important to mention that exposed conformation of Y32 was not observed in the trajectories pertaining to RAF-RBD-bound HRAS WT as shown in our earlier study Ilter and Sensoy (2019 ). Therefore, this finding suggests that exposure of Y32 might occlude the interaction interface formed between RAS and RAF-RBD and exposure of Y32 might facilitate water attacks to P γ of GTP, hence increasing intrinsic GTPase activity, in accordance with experimental data Bunda et al (2014 ).…”
Section: Resultsmentioning
confidence: 63%
“…In this study, we set out to investigate the impact of phosphorylation on the structure and dynamics of HRAS WT by performing atomistic MD simulations. Comparison of the trajectory pertaining to the phosphorylated RAS with previously obtained trajectories of GTP-bound HRAS WT and HRAS G12D Ilter and Sensoy (2019 ) showed that phosphorylation of Y32 increased the flexibility of both RAF-RBD and RAF-CRD (cysteine-rich domain) interfaces and pushed Switch I, in particular Y32, out of the nucleotide-binding pocket. Considering the fact that, exposed Y32 precluded RAF binding, we searched for molecules that could evoke similar rearrangements in HRAS G12D .…”
Section: Introductionmentioning
confidence: 85%